Comparison of hydrocarbon compositions in a sequence of humic coals, cannel coals and oil shales from the Pictou Coalfield, Nova Scotia - Püttmann, W.; Kalkreuth, W. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1989)
Thirty oil shale, cannel coal and humic coal samples from die Pennsylvanian Stellarton Group, Nova Scotia, Canada have been investigated in this study by means of organic geochemical methods including gas chromatography (GC) and gas chromatography/mass spectrometry (GC/MS). Hydrocarbon compositions of the solvent extracts were found to vary significantly with lithology and facies. Analysis of the saturated hydrocarbon fractions revealed that the relative amounts of long-chain alkanes (>CJ0) compared to those of short-chain alkanes (<C^> are higher in the humic coal than in the cannel coal and oil shale samples. Moreover, the humic coal is characterized by the presence of homodrimane as the dominant bicyclic alkane. In the oil shale and cannel coal samples, on the other hand, C, s-bicyclancs are present as major sesquiterpenoid hydrocarbons. Compounds such as biphenyl, dibenzofuran, fluorene and their mono-mediylated and di-metfiylated homologues were shown to occur almost exclusively in the aromatic hydrocarbon fractions of the humic coal samples. Presumably, these compounds are products of die degradation of lignin during diagenesis. The bitumen compositions of cannel coal and oil shale samples are quite similar.